(untitled) - Ozaeta, Antonio H. (Pasig, Metro Manila, 1991)
This book introduce about management of human enterprise. Development of the community. Operationalizing the philosophy.
Keywords: Ngân hàng và hoạt động ngân hàng,Banks and banking; Khía cạnh xã hội,Social aspects; Philippines,Philippines